Spa therapy interventions for post respiratory rehabilitation in COVID-19 subjects: does the review of recent evidence suggest a role? - Maccarone, Maria Chiara; Masiero, Stefano (Environmental science and pollution research international, 2021)
Pulmonary rehabilitation is essential in post-COVID subjects, reporting respiratory impairment after the discharge from the hospital. Because the number of patients with respiratory outcomes is high and there are few facilities available, we wonder if a spa setting could represent a valid out-of-hospital alternative. We aim to explore recent evidence related to respiratory rehabilitation in the spa environment to understand if it can represent an appropriate setting for respiratory rehabilitation interventions in post-COVID subjects. Studies were found by screening PubMed, MEDLINE, and Google Scholar databases from 2011 up to February 2021. Studies were eligible if they were reviews, randomized controlled trials (RCTs), or clinical trials, investigating respiratory interventions in the spa environment. Recent evidence has shown that inhalations and mineral-rich water immersions are effective in fighting and preventing multiple chronic respiratory tract diseases. Therefore, these treatments could also be applied to post-COVID patients with medium long-term respiratory outcomes.